2020
DOI: 10.29252/ijree.5.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Iranian Undergraduate TEFL Learners’ Self-regulation and Self-efficacy

Abstract: The present empirical study investigated the relationship between Iranian undergraduate TEFL learners' self-regulation and their self-efficacy. For this end, there have been a total number of 120 college students learning English as a foreign language who volunteered to complete the two quantitative questionnaires of self-regulation and self-efficacy respectively. The participants were informed of the anonymous nature of the data collection process in advance. They were also told that their responses would cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…For example, Morosanova and Fomina (2017) in their study concluded that self-regulation is primarily linked with anxiety and can be an important predictor of different types of anxiety namely listing anxiety. Moreover, Yazdizadeh et al (2020) found that the employment of self-regulation can help students improve their capabilities for learning and provide them with a pleasant environment for reaching their desired learning goals with low anxiety. Finally, in terms of the sub-construct of SRL (i.e.…”
Section: Self-regulated Learningmentioning
confidence: 99%
“…For example, Morosanova and Fomina (2017) in their study concluded that self-regulation is primarily linked with anxiety and can be an important predictor of different types of anxiety namely listing anxiety. Moreover, Yazdizadeh et al (2020) found that the employment of self-regulation can help students improve their capabilities for learning and provide them with a pleasant environment for reaching their desired learning goals with low anxiety. Finally, in terms of the sub-construct of SRL (i.e.…”
Section: Self-regulated Learningmentioning
confidence: 99%
“…The extent to which unfocused and focused metalinguistic feedback on the use of dependent clauses can play a role in helping L2 writers improve the accuracy of their writing continues to be an issue of interest to researchers and teachers since Truscott (1996) mounted a case for its abolition. While there is growing empirical evidence that written CF can successfully affect writing skill (Aghajani, 2018;Eshtiyaghi & Pourhossein Gilakjani, 2021;Karimnia & Heydari Gheshlagh, 2020;Yazdizadeh, Shakibaei, Namaziandost, 2020), it is unclear which feedback strategy is more effective. Some attention has been given to investigating whether certain types of written CF may be more effective than others, but the findings are not conclusive.…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…Various types of DMs are unconscious devices that serve as a pause in the middle of sentences as the speaker gathers his or her thoughts, but wants to maintain the listener's attention. DMs, in fact, add nothing to the conversions, they just help speaker to think more and organize his speaking (Yazdizadeh, Shakibaei, & Namaziandost, 2020). As words and phrases used in speaking and writing to 'signpost' discourse, DMs is useful by showing turns, joining ideas together, showing attitude, and generally, controlling communication.…”
Section: Review Of the Literaturementioning
confidence: 99%